Quantum Computing and Healthcare: Drug Discovery and Molecular Simulation with Machine Learning - Jeyalakshmi, M. S.; Sayyad, Ayesha Asif; Deepak, A.; Shrivastava, Anurag; Rao, A. Kakoli; Chakrapani, I. S.; Kumar, Navneet; Badhoutiya, Arti (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This work explores the relationship between machine learning, quantum computing, and healthcare with a particular emphasis on the development of drugs and molecular simulation. Using a descriptive design, a deductive approach, and an interpretivist philosophy, the study collects secondary data to synthesize existing literature. The analysis includes integration frameworks, machine learning algorithm designs, ethical and regulatory considerations, and simulations of quantum computing. The results shed light on the intricacies of machine learning models and quantum simulations, highlighting the necessity of strong integration frameworks to overcome compatibility issues. The regulatory and ethical landscapes need to change to accommodate quantum-enhanced healthcare technologies. The study highlights the potential for change and emphasizes that responsible implementation requires addressing technical nuances and ethical concerns.